PENGARUH TRANSFORMATIONAL LEADERSHIP DANCYBERLOAFING TERHADAP EMPLOYEE ENGAGEMENTDENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAIVARIABEL MEDIASI KARYAWAN STARTUP DI JAKARTA - Muhamad, Amar (2023)
This research is classified as a quantitative study which aims to analyze the effect of transformational leadership and cyberloafing on employee engagement with organizational citizenship behavior as a mediating variable for startup employees in Jakarta. The sample in this study were startup employees in Jakarta. Non-Probability sampling is a technique in collecting samples with purposive sampling. The data in this study were obtained through questionnaires to 96 respondents. The analytical tool in this study uses SmartPLS. This study gives the results that (1) transformational leadership has a positive and significant effect on organizational citizenship behavior. (2) Cyberloafing has a positive and significant effect on organizational citizenship behavior. (3) organizational citizenship behavior influences employee engagement. (4) Transformational leadership influences employee engagement. (5) Cyberloafing has no effect on employee engagement.